Adaptability and audience: the many publics of Etty Hillesum. (4th May 2018) - Fenoulhet, Jane
Abstract: This article considers the many adaptations of Etty Hillesum's diary in English and French and asks whether there are similarities with Anne Frank's diary which has also been mediated to many audiences through a range of adaptations. Two stage versions and their publics are then explored in more detail to reveal similar strategies for engaging audiences despite contrasting treatments of the diary.